Prototype Development for an Advanced Patient Registry to Support Collaborative Care for Common Perinatal Mental Disorders In Low and Middle-Income Countries - Chau, Chorkin (My University, 2021)
A large portion of maternal deaths are attributed to suicide, of which are related to the high rates of women affected by common perinatal mental disorders (anxiety and depression) globally. Within low and middle income countries, there are limited resources to provide adequate care for perinatal mental health, but the collaborative care model has been seen to address this problem by integrating the expertise of psychiatric consultants within primary care settings. Though it yet to be widely implemented in low-middle income countries, this study sought to understand how to adapt an advance patient registry-an essential component to the collaborative care model within two diverse settings: Ibadan, Nigeria and Can Tho, Vietnam. The study used a user-center design framework, Discover, Design, Build, and Test (DDBT) to draw insight from potential end-users of the registry to understand key functionalities, identify obstacles and facilitators of the registry use. Data was collected through interviews, focus group discussions and surveys from both contexts and responses were thematically coded in a qualitative analysis software. The results showed the value of the DDBT model in the design of the registry tool and identified the need patient centered care that incorporates routine assessments among different staff members within the clinic. Additionally, factors such as obstetric data, the inclusion of suicide risk assessment and the implementation of a risk management plan were also found to be important to include for common perinatal mental disorder care.
Thesis (Master's)--University of Washington, 2020
Keywords: Mental health; Global Health